2018
DOI: 10.1002/pssr.201800472
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Li+ Codoping in Simultaneous Improvement of Light Yield, Decay Time, and Afterglow of Lu2SiO5:Ce3+ Scintillation Detectors

Abstract: Commercially available Lu2SiO5:Ce (LSO:Ce) scintillators for the nuclear medical imaging applications, such as positron electron tomography (PET), normally have a light yield of 30 000–32 000 photons/MeV and a scintillation decay time of 43–45 ns. We demonstrate a simultaneous improvement of light yield and decay time of LSO:Ce single crystal scintillators with lithium codoping. Li codoping significantly enhances the light yield of LSO:Ce from 32 500 to 39 000 photons/MeV, shortens the scintillation decay time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…As seen in Figure , the spectrum of non-codoped LSO:Ce shows typical Ce 3+ 4f–5d absorptions. The Ce oxidation state in Cz-grown LSO:Ce single crystals has been proven to be purely trivalent by both X-ray absorption spectroscopy and electron energy loss spectroscopy. , The spectra of Cu 2+ codoped LSO:Ce samples, regardless of Cu 2+ concentration in the range less than or equal to 0.3%, also show Ce 3+ 4f–5d absorptions without the presence of the CT absorption band of Ce 4+ . It indicates that the stable Ce 3+ will not be converted into Ce 4+ with Cu 2+ codoping, dissimilar to the effect of Cu + and Ca 2+ codoping (see Figure inset). , The Cu valence state in LSO is expected to maintain +2 or reach a higher valence state (+3 or +4) rather than +1; because the Cu atoms coordinate with highly electronegative oxygen atoms in the LSO host lattice, there should be enough electron affinity and electrostatic attraction to draw off 3d valence electron(s).…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As seen in Figure , the spectrum of non-codoped LSO:Ce shows typical Ce 3+ 4f–5d absorptions. The Ce oxidation state in Cz-grown LSO:Ce single crystals has been proven to be purely trivalent by both X-ray absorption spectroscopy and electron energy loss spectroscopy. , The spectra of Cu 2+ codoped LSO:Ce samples, regardless of Cu 2+ concentration in the range less than or equal to 0.3%, also show Ce 3+ 4f–5d absorptions without the presence of the CT absorption band of Ce 4+ . It indicates that the stable Ce 3+ will not be converted into Ce 4+ with Cu 2+ codoping, dissimilar to the effect of Cu + and Ca 2+ codoping (see Figure inset). , The Cu valence state in LSO is expected to maintain +2 or reach a higher valence state (+3 or +4) rather than +1; because the Cu atoms coordinate with highly electronegative oxygen atoms in the LSO host lattice, there should be enough electron affinity and electrostatic attraction to draw off 3d valence electron(s).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The light yield can be enhanced to about 39 000 photons/MeV with 0.1 atom % Cu 2+ codoping. This result is comparable to the values achieved by Ca 2+ and Li + codoping. As the Cu 2+ codoping concentration is further increased to 0.3 atom %, the light yield drops to 18 000 photons/MeV.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ce 3+ PL decay time is shortening upon Li + or Cu 2+ co‐doping in the Y 3 Al 5 O 12 (YAG) or Lu 2 SiO 5 (LSO) hosts. [ 44–46 ] However, there, the shortening of the Ce 3+ decay time was accompanied by the increase in light yield (LY) and afterglow. The observed effects were explained by the dissociation of spatially correlated oxygen vacancies ( V O ) and Ce centers or the suppression of V O creation due to Li + co‐doping in LSO:Ce,Li.…”
Section: Resultsmentioning
confidence: 99%
“…105 Another study reported that Li doping improves the light yield of LSO:Ce by w20% while decreasing the scintillation decay time up to 42.1 ns. 106 There are also other parallel efforts in this context. It was demonstrated that 0.04% Ca co-doped LSO: Ce exhibits superior light output (35,000 photons/MeV) and shorter decay time (31 ns), rendering it the best choice for TOF-PET scanners.…”
Section: Energy and Temporal Resolutionmentioning
confidence: 99%